FAKTOR-FAKTOR PENENTU PRODUKTIFITAS KERJA PEGAWAI KANTOR SEKRETARIAT DAERAH KABUPATEN KARANGANYAR (PENDEKATAN LPM DAN MULTINOMIAL LOGISTIC MODEL) - Muhammad Wahyuddin; Narimo Narimo (Benefit: Jurnal Manajemen dan Bisnis, 2005)
The reseach aim to test impact of motivation variable to productivity of employee in localgoverment of Karanganyar. Result of the research indicated the motivation variable have negatifsignificant impact on productivity and inspection variable have positif significant impact onproductivity. Analysis of the research use multinomial logistic model (MLM).